2007
DOI: 10.1017/s1751731107694178
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of five Indian horse breeds using microsatellite markers

Abstract: The genetic relationships of five Indian horse breeds, namely Marwari, Spiti, Bhutia, Manipuri and Zanskari were studied using microsatellite markers. The DNA samples of 189 horses of these breeds were amplified by polymerase chain reaction using 25 microsatellite loci. The total number of alleles varied from five to 10 with a mean heterozygosity of 0.58^0.05. Spiti and Zansakari were the most closely related breeds, whereas, Marwari and Manipuri were most distant apart with Nei's D A genetic distance of 0.071… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
(26 reference statements)
6
16
1
Order By: Relevance
“…Results of this study are similar to those reported by Solis et al (2005), Khanshour et al (2013) and Berber et al (2014). Furthermore, Canon et al (2000), Tozaki et al (2003), Behl et al (2007) and Kusza et al (2013) reported 6, 5.8, 5.2 and 6.6 as mean numbers of alleles per locus. However, Haddad et al (2014) obtained 4.23 as a mean value in Barb and Tunisian Mogod Pony horse breeds.…”
Section: Genetic Diversity Within and Among Breedssupporting
confidence: 89%
See 1 more Smart Citation
“…Results of this study are similar to those reported by Solis et al (2005), Khanshour et al (2013) and Berber et al (2014). Furthermore, Canon et al (2000), Tozaki et al (2003), Behl et al (2007) and Kusza et al (2013) reported 6, 5.8, 5.2 and 6.6 as mean numbers of alleles per locus. However, Haddad et al (2014) obtained 4.23 as a mean value in Barb and Tunisian Mogod Pony horse breeds.…”
Section: Genetic Diversity Within and Among Breedssupporting
confidence: 89%
“…These levels for the F ST in Tunisian horse breeds are smaller than those previously found in Algerian breeds (F ST = 8.6 %, Berber et al, 2014), Polish breeds (F ST = 10 %, Zabek et al, 2005), Brazilian breeds (F ST = 11.7 %; Lippi and Mortari, 2003). However, they are slightly lower than the 6.5 % reported by Behl et al (2007) for five Indian horse breeds. The numbers of effective migrants (N m ) exchanged per generation in all breeds are presented in Table 3.…”
Section: Genetic Diversity Within and Among Breedscontrasting
confidence: 51%
“…There are reports of allergic reactions to topical products containing caffeine 22 . There are also reports of cases of dermatitis in workers who handle the coffee grains, owing to the volatile oils present as constituents of the plant 23 …”
Section: Active Botanical Ingredients Of the Products Employed In Thementioning
confidence: 99%
“…Microsatellite DNA markers, thanks to their naturally high polymorphism, can be used to analyse genetic diversity among different breeds of livestock species (Børstand et al, 2000;Canon et al, 2000;Achmann et al, 2004;Aberle et al, 2004;Solis et al, 2005;Behl et al, 2007;Bao et al, 2009;Chen et al, 2009;Kusza et al, 2009;Zrůstová et al, 2009). Molecular genetic analyses of the Old Kladruber horse using DNA polymorphism and other polymorphic systems were conducted by Hořín et al (1998).…”
mentioning
confidence: 99%